Comparison between Urine Protein: Creatinine Ratios of Samples Obtained from Dogs in Home and Hospital Settings. (8th June 2015) - Duffy, M.E.; Specht, A.; Hill, R.C.
<x xml:space="preserve">Abstract</x> Background The urine protein:creatinine ratio (UPC) is used to quantify urine protein excretion and guide recommendations for monitoring and treatment of proteinuria. Hypothesis/Objectives Home urine samples will have lower UPCs than hospital samples. The objectives were to compare UPCs of samples collected in each setting and to determine whether environment of sample collection might affect staging, monitoring or treatment recommendations. Animals Twenty‐four client‐owned dogs. Methods Prospective, nonmasked study. Clients collected a urine sample from their dog at home and a second sample was collected at the hospital. Dogs receiving corticosteroids or angiotensin‐converting enzyme inhibitors were excluded, as were those with urine samples of inadequate volume, no protein on dipstick analysis, or active urine sediment. Samples were refrigerated after collection, dipstick and sediment evaluations were completed and each sample was frozen at −80°C within 12 hours. UPCs were performed on frozen samples within 2 months. Results From 81 paired samples, 57 were excluded. Of the remaining 24, 12/24 (50%) had higher hospital sample UPCs, 9/24 (38%) had identical UPCs, and 3/24 (12%) had lower hospital UPCs. The UPCs of hospital samples were higher than home samples for the total population (P = .005) and the subset with UPC > 0.5 (P = .001). Conclusions Setting and related circumstances of urine collection in dogs is associated with UPC differences; results are usually higher in hospital than in home samples. This difference has the potential to affect clinical interpretation.